Complex systems: Introductory notes on a dialogue among political economy, evolutionary economics and physics - Eduardo da Motta e Albuquerque (PSL Quarterly Review, 2024)
Complex systems may be a useful methodological tool to address "challenges for research in development". There is a huge and growing literature on complex systems and economic theory that might be related to early intuitions of classical economists on the workings of capitalist economies. Kondratiev and Slutsky have worked with features of complex systems - how technological revolutions change the system. This may underlie one peculiarity of capitalism - a complex system that changes its level of complexity over time. The inclusion of the periphery broadens its turbulent nature: a complex system that combines regions with self-organization dynamics - the center - and regions with random behavior - the periphery.
Keywords: P16; O33; B51; 330; technological revolutions; periphery; complex systems; metamorphoses of capitalism; simulation models